Analyze the Effect of Uncertainty of Hydraulic Conductivity and Saturated Water Content of Soil within Homogeneous Earthen Dams on Seepage Values Using Seep / W Software - حسن, عز الدين; حماد, منذر; برنبو, ريم (Latakia University Journal -Engineering Sciences Series, 2020)
In this paper, we focus on determining the effect of some hydrodynamic soil parameters change (in fact, they are not fixed values) on seepage through earthen dams, thus providing the best result of simulating the actual state of any engineering construction when building a mathematical model, Hence the necessity of studying the randomness of some unsaturated soils parameters and the changes might caused in the seepage values. A mathematical model of a homogeneous earth dam was performed for steady state conditions using the Seep/W software based on the flow Equation for saturated and unsaturated soils, with the consideration of uncertainty and unreliability of hydraulic conductivity coefficient and saturated water content, after writing a code for the equations used Generate random values based on their statistical characteristics. MCSM technology was adopted to solve a very large number of simulations (4000 models for all cases studied), a deterministic model was also constructed. The research showed the effect of the obvious and significant hydraulic conductivity variation on seepage rates, while the effect of water saturation content can be neglected.